PROSPECTS FOR MODERNIZING EDUCATIONAL PROCESSES USING INTERACTIVE METHODS OF BLENDED LEARNING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article examines the concept of mixed education, its development, modern meaning and role. Describes the advantages and disadvantages of blended learning. The massive introduction of information technologies in education will lead to a change in teaching methods and the format of control, and will also require changes in the structure of education. A departure from traditional forms of education and organization of the educational process in the information society is necessary. This leads to the emergence of new learning models in educational activities.